Psychological stress assessment of patients suffering from prostate cancer. (April 2013) - Seklehner, Stephan; Hladschik-Kermer, Birgit; Lusuardi, Lukas; Schabauer, Christoph; Riedl, Claus; Engelhardt, Paul F.
Abstract Objective. The aim of this study was to assess the psychological distress of men with prostate cancer (PC) throughout the whole process from initial diagnosis to therapy and to evaluate patients' tolerance regarding treatment delay. Material and methods. This prospective study, performed between July 2007 and March 2010, evaluated the psychological distress of 28 men who underwent prostate biopsy (PB), who were confronted with a cancer diagnosis and were about to undergo radical prostatectomy (RP). Three evaluation points were defined: E1, immediately before PB; E2, after definitive diagnosis and when RP was scheduled; and E3, on the day of admission for RP. Results. Emotional distress was highest before PB, declining significantly until RP (p = 0.02). Symptoms of depression and anxiety were low at all evaluation points, with anxiety rising significantly after cancer diagnosis (p = 0.008). Concerns about postoperative erectile dysfunction and incontinence were registered at all evaluation points. Concerns about the effect on their partnership due to PC were low. The patient's tolerable waiting time for RP differed significantly from daily practice. Conclusions. Anxiety and depression as well as concerns about a negative effect on their partnership were shown to play a minor role in patients during the interval between PB and RP, while distress and concerns about erectile dysfunction and urinary incontinence were more prevalent. Support from the patient's medical and social environment and a sound partnership may have a protective effect on emotional status. Waiting time for surgery exceeded the patients' tolerated time-frames and may further contribute to the psychological distress of PC.